Achromobacter Hepatic Abscess Several Months After Laparoscopic Cholecystectomy: A Case Report and Review of Literature - Arvinder Cheema; Saadia Shafi; Sorabh Dhar (Annals of Internal Medicine: Clinical Cases)
Achromobacter xylosoxidans is a rare pathogen that causes opportunistic and nosocomial infections in immune-compromised patients. After a cholecystectomy, dropped stones can serve as nidus for abscess formation. We describe a rare case of hepatic abscess caused by Achromobacter xylosoxidans in a 40-year-old immune-competent woman who had a laparoscopic cholecystectomy 9 months previously.